Phenotypic analysis of a dwarf and deformed flower3 (ddf3) mutant in rice (Oryza sativa L.) and characterization of candidate genes - Yu-peng WANG; shuang-qin TANG; Zhi-feng WU; Qing-hua SHI; Zi-ming WU (Journal of Integrative Agriculture, 2018)
Abstracts: Dwarf mutants are the crucial resources for molecular biology research and rice breeding. Here, a rice mutant, dwarf and deformed flower3 (ddf3), was identified in tissue culture of Oryza sativa cv. Dongjin. Compared with wild type, the ddf3 mutant exhibited severe dwarfism, a greater number of tillers and significantly decreased fertility. In addition, leaf length, panicle length, and grain length, were significantly shorter. All internodes of ddf3 were shorter than those of wild type, and histological analysis revealed that internode cell elongation was significantly inhibited in ddf3. In the ddf3 mutant, pollen activity was significantly decreased, and the development of most stigmas was abnormal. Genetic analysis indicated that the ddf3 mutant phenotypes are controlled by a single or tightly linked nuclear genes. Using an F2 mapping population generated from a cross between ddf3 and Yangdao 6 (9311), the DDF3 gene was mapped to a 45.21-kb region between insertion-deletion (InDel) markers M15 and M16 on the long arm of chromosome 7. Sequencing revealed a 13.98-kb-deletion in this region in the ddf3 mutant genome that resulted in the complete or partial deletion of ZF (DHHC type zinc finger protein), EP (expressed protein), and FH2 (actin-binding FH2 domain-containing protein) genes. Quantitative RT-PCR analyses revealed that in wild type, the transcript levels of FH2 were almost the same in all organs, while ZF was mainly expressed in the panicle, and no expression of EP was detected in any organ. Based on these results, ZF and FH2 could be potential DDF3 candidate genes involved in the regulation of rice morphology and flower organ development. Our work has laid the foundation for future functional analysis of these candidate genes and has provided a profitable gene resource for rice breeding for increased fertility in the future.